2021
DOI: 10.1103/physrevlett.126.244801
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Wave-Particle Duality in Free-Electron–Bound-Electron Interaction

Abstract: We present a comprehensive relativistic quantum-mechanical theory for interaction of a free electron with a bound electron in a model, where the free electron is represented as a finite-size quantum electron wave packet (QEW) and the bound electron is modeled by a quantum two-level system (TLS). The analysis reveals the wave-particle duality nature of the QEW, delineating the point-particle-like and wavelike interaction regimes and manifesting the physical reality of the wave function dimensions when interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…We first describe our unified theory for the quantum three-particle interaction of a free electron, a bound electron, and a photon in a single-mode cavity. Assuming that the bound-electron system is a two-level emitter, we can readily use the Jaynes-Cummings (JC) (45,46) and the free-electron bound-electron resonant interaction (FEBERI) (39)(40)(41)47) models for its coupling to the cavity photon and the free electron, respectively. The coupling of the free electron and the cavity photon is generally captured by the quantum photon-induced near-field electron microscopy (QPINEM) (35,37,48,49) model.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…We first describe our unified theory for the quantum three-particle interaction of a free electron, a bound electron, and a photon in a single-mode cavity. Assuming that the bound-electron system is a two-level emitter, we can readily use the Jaynes-Cummings (JC) (45,46) and the free-electron bound-electron resonant interaction (FEBERI) (39)(40)(41)47) models for its coupling to the cavity photon and the free electron, respectively. The coupling of the free electron and the cavity photon is generally captured by the quantum photon-induced near-field electron microscopy (QPINEM) (35,37,48,49) model.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Using a fully quantum-mechanical analysis (both free and bound electrons quantized) of the FEBERI interaction with a single arbitrarily shaped QEW [34,35], we showed that the FEBERI effect can be applied for coherent control and interrogation of the qubit state of a target TLS. However, because the FEBERI effect is practically very weak for a single QEW and single TLS, it is necessary to consider the interaction of the TLS with multiple modulation-correlated QEWs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the optical dipole force could be applied to trapping and transporting nanoparticles or atoms [13][14][15][16][17][18][19]. Recently, the optical fields in photonic microstructures have been applied to manipulate free electrons [20][21][22], which provide new tools to investigate and control both photons and electrons [23][24][25][26][27][28][29]. For the the manipulation of photons, the interaction could accumulation with the propagation of photons when phase-matching condition of nonlinear optics effect is satisfied for a given device and working wavelength [30].…”
mentioning
confidence: 99%